THE PERSPECTIVE OF PRAGMATICS IN THE JAVANESE DAILY CONVERSATION - R. Kumbino Ari Soedhono, S.S., M.Pd. Kumbino Ari Soedhono (FEB UNTAG Semarang, 2020)
At present day, people agree that pragmatics is familiar in the field of linguistics. Pragmatic is not only studying meaning of utterances or words – as semantics does – but also exploring the interactions between two or more people in doing their communication. On the other hand, pragmatics is the study of meaning in a particular context and situation. Based on the opinion above, this study is aimed at investigating the pragmatic relationship between speech act and social conditions in Javanese society. In this case, this paper will be concerned with the influences of speech acts and social conditions to the meaning interpreting. The method of collecting data used is document/library study (secondary data). The data which have been collected are analyzed qualitatively. After analyzing the data, it is found that speech acts and social conditions influence people in their communication. At the end of the paper, conclusion drawn is that studying a language is not only studying its rules, grammar, pronunciation, and meaning, but also studying its process of thinking and its social condition (psychological and sociological process) as well.